2020
DOI: 10.1363/psrh.12169
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Based Doulas and COVID‐19: Addressing Structural and Institutional Barriers to Maternal Health Equity

Abstract: The Black-White racial disparities in maternal and infant health outcomes are among the largest disparities seen in traditional perinatal health measures. 1,2 Black pregnant and postpartum people * have a pregnancy-related mortality ratio that is three to four times that of their White counterparts, and disparities in severe maternal morbidity are similar. 3-5 Additionally, the infant mortality rate among Black neonates is more than twice that of White neonates (10.8 vs. 4.6 per 1,000 live births), 6,7 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Prior studies also have shown that pregnant women who interact with their doulas early in pregnancy are more engaged in their prenatal care and have better birth outcomes. 24 Doula care received during early in pregnancy, therefore, may shift women into a trajectory that ultimately results in improved health outcomes during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies also have shown that pregnant women who interact with their doulas early in pregnancy are more engaged in their prenatal care and have better birth outcomes. 24 Doula care received during early in pregnancy, therefore, may shift women into a trajectory that ultimately results in improved health outcomes during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…While some institutions facilitated connections to outside doula support, other healthcare settings restricted even video calls during delivery ( 19 ). The challenges faced by community-based doula organizations to transition to virtual services and the lack of technological access among mothers continue to hinder virtual doula support, and compound existing inequities ( 20 ). Moreover, Combellick et al ( 21 ) have documented lack of clear information from healthcare providers and unnecessary interventions during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…21 The syndemic of health care disparities among ethnic/ racial minorities and COVID-19 further increases the risk of serious maternal morbidity and death. [22][23][24][25][26][27][28] Acknowledging the crucial opportunity to develop resources to support equitable obstetric care during the COVID-19 pandemic, SMFM outlined challenges to overcome, which include telehealth access and confronting bias, among many others. 29…”
Section: Racial Discrepancies In Covid-19 Morbidity and Mortalitymentioning
confidence: 99%